Sintesis dan Karakterisasi Nano-Hidroksiapatit dari Cangkang Rajungan Sebagai Material Pembuatan Filament 3D Printing dengan Kombinasi Poly(caprolactone) - Wiyono, Deden Eko; Siregar, Salma Auliarifkie; Ma'mun, Ummu Zahroh; Rosanti, Maharani Sugito; Ningrum, Eva Oktavia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
An orthopedic anchoring rotator cuff is often used to reattach a torn rotator cuff tendon to the bone.  However, anchoring rotator cuffs commonly use non-biodegradable metals and require a second surgery. Furthermore, manufacturing processes for retaining rotator cuff implants are developed using filament-based 3D printing. So that biodegradable and biocompatible materials are needed as filament materials for making anchoring rotator cuffs, one of which is by mixing poly(caprolactone) (PCL) and hydroxyapatite (HAp). In this research, we will synthesize nano-sized HAp from crab shell waste using the precipitation method. The synthesis results will be reviewed through XRF, FTIR, XRD, and SEM analysis. In addition, the mechanical properties of PCL/HAp composite filaments for tissue scaffolds at variables of 9.5:0.5, 9:1, and 8.5:1.5 were also reviewed. XRF characterization results show that the crab shell has a calcium content of 93.09%. FTIR testing shows the formation of hydroxyapatite functional groups, namely OH- and PO43. XRD test results show conformity with the JCPDS 09-0432 graph with a degree of crystallinity of 88.32%. SEM analysis showed that the HAp produced has a nano size with a particle diameter of about 126.3 nm. In mechanical analysis, the best PCL/HAp filaments were obtained at a mixing ratio of (9:1)